Cosmopolitismo em panoramas móveis : comunicação, práticas de consumo e cidadania de sujeitos em mobilidade internacional, no contexto das cidades globais São Paulo e Londres - Riegel, Viviane (2019)
The central objective of this thesis is to analyze the possible and different experiences of cosmopolitanism that the individuals in international mobility live in their daily practices of consumption and citizenship in the socio-communicational spaces of London and São Paulo. In order to study these experiences, a comparative cartography was carried out based on the different individuals, spaces and practices in each city - and between them. The theoretical references for the development of this discussion are formed by 1) reflections on cosmopolitanism, its different concepts; 2) everyday practices of consumption and citizenship; 3) global cities and their socio-communicational spaces; 4) individuals in international mobility. The field research carried out consists of 1) interviews with 20 individuals in different mobility experiences in each city; 2) observation of the practices of individuals in 16 socio-communicational spaces most mentioned by the interviewees. The qualitative methodological approach is based on the theory of global culture´s scapes, proposed by Appadurai (1996), using the cartography method, supported on the Martin- Barbero mediations mapping categories (2009). As main results, we found differences between individuals living in the same city (mainly by social distinctions, especially by income and race), as well as shared issues between individuals living in different cities, but experiencing both access (higher income groups of the Global North) as well as barriers (lower income groups of the Global South), both in São Paulo and in London. In the mapping of the citizenship and consumption practices of the researched individuals, in the interactions and mediations with socio-communicational spaces, we find references of global consumption and contact with the country of origin through media and cultural consumption, as well as barriers to access to rights and processes of mobilization and activism, mainly through digital media, in the search of amplification of citizenship. From their practices and conditions, individuals in international mobility in São Paulo and London, find possibilities to experience cosmopolitan experiences in the spaces of these cities in different ways. In the case of higher income groups, consumer practices and the connection with products and services that reflect a neoliberal logic of cosmopolitanism. In the case of lower income groups, in the sharing of issues related to rights and the possibilities of living the experience of international mobility, with a liberating perspective on citizenship.